Analysis and Optimization of the Usability of E-Commerce Platforms through Evaluation Heuristics - Alejandra Yicel Vargas Muñoz; Antoni Granollers i Saltiveri; Cesar Alberto Collazos Ordoñez (CLEI Electronic Journal)
This paper extends previous work on usability evaluation heuristics for e-commerce platforms by conducting a detailed experimentation to validate and refine the proposed heuristic set. A group of international expert evaluators applied the new heuristics to an e-commerce platform, providing both individual assessments and qualitative feedback. The results revealed significant insights into the platform's usability, highlighting strengths and areas needing improvement. This process not only identified deficiencies but also allowed for the adjustment and optimization of the heuristic questions to better reflect user needs and expectations. The validated heuristics, which include 15 guidelines and 60 questions, provide a comprehensive evaluation framework, quantifying usability through a percentage score. The findings contribute to the ongoing enhancement of e-commerce platform usability and offer valuable knowledge for the usability and user experience research community.